Effects of Spirulina platensis on alloxan induced diabetic rats (Progressive Agriculture, 2018)
The study was undertaken to investigate the effects of Spirulina platensis on body weight, blood glucose and lipid profile on alloxan induced diabetic rats. Fifteen Long Evans male rats at six weeks of age were used for the experiment. Diabetes was induced by intraperitoneal injection of alloxan@ 150 mg/kg and experiment was carried out for a period of 6 weeks. Rats were divided into three groups of 5 rats each. The groups were i)healthy control, ii) diabetic control with both receiving rats’ pellet as supplement, and iii) diabetic treated with oral administration of Spirulina platensis  @ 400 mg/kg bwt. Results from the study showed that Spirulina platensis reduced blood glucose significantly (P